A numerical and experimental analysis of an integrated TEG-PCM power enhancement system for photovoltaic cells. (15th August 2019) - Darkwa, J.; Calautit, J.; Du, D.; Kokogianakis, G.
Highlights: TEG power output was relatively small due to small temperature difference. The PV/TEG/PCM system achieved 9.5% power output more than other systems. 50 mm thick PCM layer achieved the best performance for the PV/TEG/PCM system. Abstract: Solar photovoltaic (PV) cells especially crystal silicon cells have witnessed a soaring installed capacity during past years. Research efforts have been made to increase the PV conversion efficiency and one direction is towards the cooling of PV systems since a higher PV temperature impairs its conversion efficiency. Phase change materials (PCM) capable of storing large amounts of latent heat are found to be effective on cooling PV cells while thermoelectric generators (TEG) which are solid waste heat converters can be used for converting the heat from PV into electricity. Therefore, this research investigates the concept of an integrated thermoelectric PCM system to enhance the PV efficiency. Theoretical investigations found that the TEGs had small power output due to small temperature difference under natural convection conditions. However, PCM was effective on hampering PV temperature increase during heat storage process. This research developed a numerical model for thermal simulations of the integrated system and has been validated by experimental results. The effect of various PCM thicknesses, conductivities and phase change temperatures were evaluated. The simulation results stressed the importance of high PCM conductivity for a thick PCM layer to reduce its insulation effect on the TEG and PV layers. Finally, the best thermal performance for the PV/TEG/PCM system was achieved with a 50 mm thick PCM layer with thermal conductivity of 5 W/m K and a phase change temperature of 40–45 °C. Further optimisation and experimental evaluation are however being recommended towards the establishment of the full technical and scientific boundaries.